Exploring The Benefits Bilingualism: In Group Disscussion - Virgiananda Sucinur Hermawan; Virly Aufa Nada Triana; Lusiana Suciati Dewi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Bilingualism in the 21st century is becoming increasingly relevant and important in the context of increasing globalization, technology, and social mobility. Like the word psychology, which just joined the world of education in the 20th century. The development of psychology is psycholinguistic. Bilingualism in group discussions provides many advantages in both academic and professional settings. Besides, bilingualism can be used in everyday life and acts as a communication bridge for interlocutors who are in the neighborhood of a variety of areas. This research is qualitative, with a qualitatively descriptive approach. The data came from a group of English-language education students and was obtained through observational research instruments and interviews. The data referred to in this study covers some of the benefits of bilingualism in group discussions. It can be concluded that this study found some benefits of bilingualism for group discussion by FKIP University Subang English Education Students through interviews with several students. The findings of the study yielded significant benefits to the students: improved communication skills, facilitated interaction with members, increased confidence, and added new vocabulary.